2020
DOI: 10.1097/pq9.0000000000000264
|View full text |Cite
|
Sign up to set email alerts
|

A Quality Improvement Intervention Bundle to Reduce 30-Day Pediatric Readmissions

Abstract: Introduction: Pediatric hospital readmissions can represent gaps in care quality between discharge and follow-up, including social factors not typically addressed by hospitals. This study aimed to reduce the 30-day pediatric readmission rate on 2 general pediatric services through an intervention to enhance care spanning the hospital stay, discharge, and follow-up process. Methods: A multidisciplinary team developed an intervention bundle based on a nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…History of prior hospital admissions, medical complexity, and non-acute post-discharge were found important features in predicting readmission, which is consistent with the previous investigations [22,24,28,49]. Although these factors are not easily modifiable for most conditions, comprehensive intervention strategies including better discharge planning (e.g., telephone call) and care coordination can mitigate the risk of pediatric readmission [13,31,50,51]. The findings of prior hospital visits in all three readmission models suggest that there might exist an unresolved system issue associated with the quality and clarity of discharge education and access to pediatric care for a certain patient population [36].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…History of prior hospital admissions, medical complexity, and non-acute post-discharge were found important features in predicting readmission, which is consistent with the previous investigations [22,24,28,49]. Although these factors are not easily modifiable for most conditions, comprehensive intervention strategies including better discharge planning (e.g., telephone call) and care coordination can mitigate the risk of pediatric readmission [13,31,50,51]. The findings of prior hospital visits in all three readmission models suggest that there might exist an unresolved system issue associated with the quality and clarity of discharge education and access to pediatric care for a certain patient population [36].…”
Section: Discussionsupporting
confidence: 87%
“…Compared to adult and Medicare readmission rates, pediatric readmission rates remained unchanged, and one study even reported a national increment (8.2%) between 2010 and 2016 [11,12]. Consequently, readmission reduction efforts gained significant recent attention among healthcare providers and professionals in devising ways of reducing readmission risk among children [13,14]. An improved readmission prediction model could help hospitals and healthcare providers to identify high-risk patient groups and, implement interventions in timely manner that reduce the risk of unplanned readmission within days of discharges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When parents of CMC reported unmet social needs (i.e., “positive” response to ≥ 1 items in the SSNAC questionnaire), a standardized approach guided complex care program staff’s assessment and response. Assessment of reported unmet social needs was guided by a template developed in collaboration with long-standing partners from Legal Aid of North Carolina’s statewide Medical-Legal Partnership program [ 26 ]. The assessment template was tailored to correspond with SSNAC screening questions and provided staff with the following approaches for response to unmet social needs: (a) providing information to families about how to meet the social need; (b) directly assisting the family with their social need; and/or (c) making a direct referral to a community-based agency/partner with additional resources and expertise to meet the need.…”
Section: Methodsmentioning
confidence: 99%
“…Given the significance of hospital variation in readmissions, a systems-based approach may be necessary to prevent readmissions and improve hospital quality. Evidence suggests that discharge transition plans, follow-up care, and addressing adverse social determinants of health are useful interventions to reduce hospital readmission rates [44,45].…”
Section: Discussionmentioning
confidence: 99%